Pengaruh Merek, Reputasi, Kualitas Pelayanan dan Lokasi terhadap Proses Keputusan Nasabah Menggunakan Produk Tabungan di BJB Syariah, Ciputat - Umiyati Umiyati; Nadiyya Syaima (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2018)
The study aims to examine and analyze the influence of brand, reputation, service quality, and location of customer decisions in BJB Syariah. The sample in this study were taken by using the data collection method called purposive sampling. The number of samples used were 60 respondents. The data obtained were analyzed by using Partial Least Square analysis technique through the PLS software version 3.2.7. The result showed that: (1) brand has a significance influence on customer decisions; (2) reputation hasn’t a significant influence on customer decisions; and (3) service quality has a significant influence on customer decisions (4) and also location has a significance influence on customer decisions.